Digital payment technologies and interbank clearing in the Republic of Kazakhstan in terms of digitalization - Saifullina, Yu.M.; Serikova, G.S.; Assanova, M.A.; Amirova, G.N.; Akenov, S.Sh. (BUKETOV BUSINESS REVIEW, 2021)
Object: To analyze background and implementation conditions of national digital currency in Kazakhstan in the conditions of digitalization and forecast the development of digital money in Kazakhstan using economic and statistical modelling. To develop the electronic money circulation system, second-tier banks, which are the main subjects of the financial market, provide remote services, develop strategies for general development, which prescribe rational ways to attract customers to remote service, apply modern technologies and improve the system of cashless money circulation, both nationally and internationally. Methods: Statistical resources of the Committee of statistics of the Ministry of National economy of the Republic of Kazakhstan were used in the paper. Methods of deduction and systematization were applied. In this study an extrapolation forecast was made for the indicator “the volume of payments in the interbank money transfer system and the interbank clearing system” for 2021-2023. Results: Nowadays financial ecosystems based on digital technologies are being actively implemented. This trend is noticed in different countries of the world. It opens new possibilities for development of national currencies. Commercial banks are creating new types of digital money by incorporating them into traditional economic interactions. Conclusion: Kazakhstan is a perspective region for the implementation of its own digital currency. The country's unique geographical position, economic relationships with China, Russia and the West, the presence of international technology giants in the country make the electronic tenge a popular financial instrument that will significantly improve the competitiveness of the Kazakhstani economy, increase its attractiveness with similar projects from other countries at the global level. The concept of introducing digital currency and its transition to widespread use in Kazakhstan will ensure not only the creation and development of completely new ecosystems of financial products and services, but also the modernization of existing “traditional” ones.